Populism, participation, and political equality. Issue 1 (11th February 2019) - Anduiza, Eva; Guinjoan, Marc; Rico, Guillem
Abstract: This article analyses the relationship between populist attitudes and political participation. We argue that populist attitudes can be a motivation for participation through their identity, emotional, and moral components, and that they have the potential to narrow socioeconomic gaps in participation. Using survey data from nine European countries, our results show that populist attitudes are positively related to expressive non-institutionalized modes of participation (petition signing, online participation and, in some contexts, demonstrating), but not to turnout. In addition, populist attitudes are found to reduce education-based gaps and even reverse income-based inequalities in political participation. The implications of these findings are discussed.